Efektivitas konseling behavioral dengan teknik self-management untuk meningkatkan disiplin belajar siswa - Dio Rizky Adirama; Putu Ari Dharmayanti; Dewi Arum Widhayanti Metra Putri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The research was conducted with the intention of seeing the effectiveness of behavioural counselling theory with self-management techniques in the improvement of student study discipline. In the design of this study, a quasi-experimental design with a non-equivalent post-test control group design was used. Participants were 10th grade students from SMK Negeri 2 Singaraja. The sampling was carried out by means of random sampling of the class as an attack group. As for the members of the sample are students of class X kuliner 5 and X kuliner 6, total 69 people as experimental and control class. The method used to analyse the data is the t-hit test using the program SPSS v.25 for Windows. The data collection instrument used is the study discipline questionnaire. This study uses behavior theory with self-management techniques to improve learning discipline among students in grade X in SMK Negeri 2 Singaraja. Based on the results of this study, t=2.705 and ES=0.64, p<0.05, we can accept Ha and reject Ho.